The Routine Histopatological Examination-Chicken with Suspect Coryza (Stress Related Disease) - Haryo, Albiruni; Enola, Janice (Veterinary Biomedical and Clinical Journal, 2019)
Coryza (snot) kown as respiratory disease in chickens caused by Haemophilus paragalinarum. Coryza is a disease that often occurs and results in large economic losses impact. The aim of this study was to look and diagnose changes in macroscopic and microscopic (histopathology) in chickens that have been examined and suspected of Coryza (snot) disease. The organs examined are palpabrae (eyes), trachea, pancreas and cerebellum. Examining and observing macroscopic changes, swelling of the palpabrae, tracheal hemorrhages and pancreatic hemorrhages and cerebellum were normal. Microscopic changes seen in palpabrae are oedema, hemorrhage and blood clot found, tracheal epithelial erosion, hemorrhage, multiplication of goblet cells and inflammatory infiltration of PMN cells, pancreas shownÂ  there is an inflammatory cell infiltration and fibrosis necrosis, and infiltrating cell inflammation in cerebellum. From examinations and observations it can be concluded that macroscopic and microscopic changes lead to the suspected Coryza (snot) disease.